Social Entrepreneurship and Sustainable Development in South Africa - Dzomonda, Obey (Journal of Reviews on Global Economics, 2020)
The purpose of this paper was to demystify the role of social entrepreneurship as a vehicle towards sustainable development in South Africa. This study adopted a quantitative research design as it intended to obtain and analyse numerical data. Data was collected using a self-administered questionnaire in a survey. A sample of 60 social entrepreneurs was conveniently sought to participate in the study. Data was analysed using factor analysis and regression analysis. Reliability of constructs was tested using the Cronbach’s alpha. Descriptive statistics showed that the surveyed social entrepreneurs possess high levels of social entrepreneurship as measured by empathy, moral obligation, social mission and social innovation scales. The regression results validated the key role of social entrepreneurship towards sustainable development in South Africa. A significant and positive relationship was established between SE and ECS (β, 0.691; p.0.011) and between SE and SS (β, 0.431;p.0.002). On the other hand, no significant relationship was found between SE and ES (β, 0.052; p.0.321). The paper concludes that developing a huge social entrepreneurship base will immensely contribute towards the attainment of sustainable development in South Africa. Recommendations were made for the government to launch policies favouring social entrepreneurship growth.